Environmental trends during the Bronze Age recorded in paleosols buried under a big kurgan in the steppes of the Ponto-Caspian area. (10th May 2021) - Khokhlova, Olga; Sverchkova, Alena; Myakshina, Tatyana; Makeev, Alexander; Tregub, Tamara
Abstract: The southern steppes of European Russia are rich in archaeological monuments that were extensively studied for many decades. Nevertheless, paleosols buried under the burial mounds and especially the big kurgans of the Bronze Age in the Ponto-Caspian area did not receive proper attention. The paper focuses on soil evolution and climate dynamics during the Bronze Age based on the study of soils buried during several stages of earthen mound construction within one big kurgan in the Kuban-Azov Plain, Russia. The kurgan 1 in the Beysuzhek-9 kurgan cemetery of the Bronze Age, situated in the Korenovsky District, Krasnodar Region, consists of three earthen mounds made at different times. The soils, buried under three mounds of the kurgan, are located in close vicinity from each other and have similar lithology and geomorphic position. They form a chronosequence representing three time slices. Moreover, the chronosequence displays a certain chronological order of burial: paleosols were first buried in the center of the kurgan and later closer to its periphery. The height of the kurgan is about 4 m that ensures good preservation of the buried soils. The research is based on the comparative analysis of morphology, micromorphology and analytical properties of three paleosols buried under different constructions in the kurgan and surface soil. Also, the palynological analysis was performed for the uppermost layers (0–5 cm) of three paleosols. During the first stage of the kurgan construction, the Novotitorovo archaeological culture of the Early Bronze Age at the 27th-22nd centuries BC, the climate of the region was sufficiently humid and provided a high bioproductivity for surrounding landscapes. The interval between the second and third stages of kurgan construction was marked by the gradual increase in aridity. During the third stage of the kurgan construction (the Catacomb archaeological culture, the Middle Bronze Age, the 21st −16th centuries BC), the climate was mostly arid. The results of the palynological analysis are in agreement with the study of paleosols. During the construction of the kurgan, the vegetation pattern corresponded to a Southern forest-steppe. The percentage of herbaceous plants increased markedly, and steppe species appeared during the time of Catacomb culture.